Pendampingan Identifikasi Isu Kebijakan dan Penyusunan Policy Brief bagi Pejabat Eselon III Pemerintah Kabupaten Way Kanan - Syarief Makhya; Maulana Mukhlis (Jurnal Pengabdian Pada Masyarakat, 2021)
POLICY ISSUES IDENTIFICATION AND THE MAKING PREPARATION OF POLICY BRIEF FOR ECHELON III OFFICIALS OF WAY KANAN DISTRICT. The ability to set agendas in a comprehensive approach from the stage of identifying policy issues or public issues to compiling recommendations in the form of policy briefs has not been widely carried out within Way Kanan District. Therefore, the targets in this service are (a) disseminating understanding of the role of local governments in solving public problems through various public policy approaches; (b) giving participants an understanding of the characteristics of public policy issues and (c) providing technical skills in preparing a policy brief. Through mentoring methods (lectures, outreach, counseling, and preparation practices), the results of service supported from pre-test and post-test data have been able to improve the aspects of knowledge, attitudes, and commitments of echelon III officials regarding concepts and strategies for identifying issues and formulating policy briefs as well as making a positive contribution to increase the awareness and confidence of echelon III officials in formulating policy recommendations and public policy making practices in Way Kanan District. In terms of behavior, the service instrument shows optimism that the quality of public policies created by Way Kanan Regional Government will be better, both in terms of the preparation process and in the aspects of policy substance.